(untitled) (Politeja, 2025)
The main objective of the article Death in Korea – Folklore and Rituals related to understanding of the underworld is to analyze the meaning of death in traditional Korean culture. To achieve this goal, it is necessary to discuss original Korean beliefs related to the afterlife. The article will therefore present and discuss Korean folk stories related to the underworld, its inhabitants and the ways to get into it. To further emphasize the importance of death in Korean culture, the article will examine the rituals that ensure the proper passage of the deceased into the afterlife.